Tumor suppression, dose-limiting toxicity and wellbeing with the fetal estrogen estetrol in patients with advanced breast cancer - Schmidt, Marcus (J Cancer Res Clin Oncol, 2020)
PURPOSE: The aim of this study (the ABCE4 study) was to assess dose-limiting toxicity (DLT), safety, tolerability and preliminary efficacy of high doses of the fetal estrogen estetrol (E4) in postmenopausal patients with heavily pretreated, locally advanced and/or metastatic ER+/HER2−breast cancer, resistant to anti-estrogens. METHODS: This was a multicenter, open-label, phase IB/IIA, dose-escalation study with a 3 + 3 cohort design, whereby successive cohorts of three patients received 20 mg, 40 mg or 60 mg E4 per day for 12 weeks by oral administration. DLTs, safety and wellbeing were evaluated after 4, 8 and 12 weeks of treatment. Anti-tumor effects were investigated by computer tomography scanning and evaluated according to RECIST criteria before and after 12 weeks of treatment. Wellbeing was judged weekly by the investigator and by quality-of-life questionnaires by the patients. In view of the small number of patients, no statistical testing was performed. RESULTS: All 12 patients enrolled had progressive, heavily pre-treated advanced breast cancer. No treatment-related serious adverse events or DLTs occurred during the first 4 weeks of E4 treatment allowing the investigation of all three doses. Five of nine patients completing 12 weeks of E4 treatment showed objective anti-tumor effects and six of nine patients reported improved wellbeing. CONCLUSION: High doses of estetrol seem to be safe and are well tolerated during 12 weeks of treatment without dose-limiting toxicity and with anti-tumor effects in five of nine heavily treated patients with progressive, anti-estrogen resistant, advanced breast cancer.